GIS based morphometric analysis of a forest watershed in lower Shivaliks of Punjab using high resolution satellite data - PRASAD, VISHNU; YOUSUF, ABRAR; SHARMA, NAVNEET (Journal of Soil and Water Conservation, 2020)
Management of natural resources particularly soil and water is very important. The watershed is considered to be the ideal unit for management of natural resources. Remote sensing and GIS, being efficient, accurate and time saving techniques have found great relevance for management of natural assets. In the present study, remote sensing and GIS have been used to evaluate the morphometric parameters of the Dada watershed located in the lower Shivaliks of Punjab. The high resolution ALOS PALSAR digital elevation model having spatial resolution of 12.5 m has been used for calculating various morphometric parameters such as linear, aerial and relief aspects of the watershed morphometry. Morphometric parameters such as stream order, stream length, drainage density, stream frequency, circulatory ratio, form factor, bifurcation ratio, elongation ratio, compactness coefficient etc. have been evaluated. The total area and perimeter of the study watershed is 1491.1 ha and 29.1 km, respectively. The results of the study revealed that the Dada watershed is 5th order watershed. It was observed that total number of streams in the study watershed is 377 out of which 216 are of 1st order, 94 are of 2nd order, 60 are of 3rd order, 6 are of 4th order and 1 is of 5th order. The total lengths of all stream is 71.98 km and mean stream length is 190.92 m. Drainage density of the watershed is 4.83 km/km2. Drainage texture and length of overland flow are 30.45 no./km and 2.414 km, respectively. The watershed is having stream frequency of 25.28 no./km2 and mean bifurcation ratio of 4.97. The watershed has form factor of 0.27, circulatory ratio of 0.22 and the elongation ratio of 0.586. The present study is constructive discourse to comprehend the hydrological behaviour of the watershed. It would be useful for planning and implementation of soil and water conservation measures in the Dada watershed.